Diseño del modelo para la integracion y propuesta de implementacion de las normas NTC-ISO 9001:2008 y NTC-ISO/IEC 17025:2005 para el laboratorio de suelos de la Universidad Distrital Francisco José de Caldas (2015)
The implementation and accreditation of the Integrated Management Systems to the soil laboratories, allows them to position themselves in the market, give recognition and credibility of the services provided by it and achieve the satisfaction of the interested parties. However, by requiring certain organizational changes, various difficulties may be encountered during the implementation process, such as resistance to change and / or the need for additional resources, the need for more staff training, among others. This is why, based on the process approach, this document seeks to design an integrated management model, based on the standards NTC-ISO 9001: 2008 and NTC-ISO / IEC 17025: 2005 that unifies the requirements established in both norms and that allows the Soil Laboratory of the Francisco José de Caldas District University through its implementation, the achievement of the institutional objectives, make its processes more efficient through the continuous improvement of the system, reduce the duplication of information, increase confidence in the laboratory by providing results that are technically sound and that demonstrate the technical capacity of the laboratory.